2019
DOI: 10.1007/s11027-019-09860-x
|View full text |Cite
|
Sign up to set email alerts
|

Negative emissions of carbon dioxide through chemical-looping combustion (CLC) and gasification (CLG) using oxygen carriers based on manganese and iron

Abstract: Carbon capture and storage (CCS) is an economically attractive strategy for avoiding carbon dioxide (CO 2) emissions from, e.g., power plants to the atmosphere. The combination of CCS and biomass combustion would result in a reduction of atmospheric CO 2 , or net negative emissions, as plant growth is a form of sequestration of atmospheric carbon. Carbon capture can be achieved in a variety of ways, one of which is chemical looping. Chemical-looping combustion (CLC) and chemical looping gasification (CLG) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Previous investigations have shown that the BCLG process represents a good option for syngas production with low tar generation, because the presence of an oxygen carrier in the system helps its reduction. 5 , 12 , 16 It was observed that the operational variables with the greatest impact on the tar content were the fuel reactor temperature and the steam/biomass ratio.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous investigations have shown that the BCLG process represents a good option for syngas production with low tar generation, because the presence of an oxygen carrier in the system helps its reduction. 5 , 12 , 16 It was observed that the operational variables with the greatest impact on the tar content were the fuel reactor temperature and the steam/biomass ratio.…”
Section: Resultsmentioning
confidence: 99%
“…If CO 2 formed during combustion is captured and then stored [bioenergy with carbon capture storage (BECCS) technologies], it is possible to achieve net-negative CO 2 emissions into the atmosphere. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, the utilization of fossil fuels has been considered as one of the biggest problems to the increasing emission of CO 2 . Chemical looping has emerged as a promising technology for coal utilization as it decreases the irreversible entropy production to increase the energy utilization efficiency. , It takes advantage of the redox behavior of oxygen carriers (OCs) between two individual reactors to realize initial CO 2 separation and NO x emission control without the enrollment of pure oxygen. In situ gasification chemical looping combustion (CLC) is known as a typical strategy for coal utilization for complete oxidization between the fuel and the OC in the reducer. , Conversely, chemical looping gasification (CLG) was proposed to achieve plenty of syngas (H 2 and CO) through partial oxidization, as is shown in Figure .…”
Section: Introductionmentioning
confidence: 99%